LEARNING STRATEGIES INVOLVING PLAY AND COORDINATION: A PATHWAY TO IMPROVING MOTOR SKILLS - Desy Waryanti; Umar Umar; Muhammad Sazeli Rifki; Masrun Masrun (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study examines the impact of play-based learning methods and coordination exercises on motor skills, specifically the volleyball serve technique, at Junior High School (JHS) 19 Bintan. The research utilized a quasi-experimental 2x2 factorial design, involving 20 students from grade VII, categorized based on their motor skills into high and low groups. The volleyball serve skills were assessed using the AAHPER Serving Accuracy Test, while motor skills were measured through tests of strength, speed, agility, power, and coordination. Data analysis was performed using two-way ANOVA. The analysis revealed that the overall model was statistically significant (F=89.378, p=0.000), explaining 93.3% of the variance in volleyball serve performance. However, the main effect of teaching methods (F=58.800, p=0.130) and motor ability (F=202.800, p=0.152) were not statistically significant. Additionally, the interaction between teaching methods and motor ability did not yield a significant result (F=6.533, p=0.421). Descriptive statistics indicated that students with higher motor abilities, particularly those exposed to play-based methods, showed improved performance in overhand serve skills. While the results did not reach statistical significance, these trends suggest that integrating play-based learning with coordination exercises may have practical benefits for enhancing motor skill development, particularly in sports that require technical precision, such as volleybal.